The crimson petal and the white [videorecording (DVD)] - Munden, Marc; Garai, Romola, 1982-; O'Dowd, Chris, 1980-; Hale, Amanda, 1982-; Henderson, Shirley, 1965-; Gatiss, Mark; Grant, Richard E., 1957-; Anderson, Gillian, 1968-; Faber, Michel (Acorn Media, 2012)
In 1870s London, a prostitute known as Sugar sees a potential way out of the brothel she works for when she is taken in by William Rackham, the son of a wealthy businessman.